2005
DOI: 10.1308/1478708051793
|View full text |Cite
|
Sign up to set email alerts
|

A team approach to musculo-skeletal disorders

Abstract: The team's experience demonstrates the effectiveness of a team approach in tackling what is often seen as the insoluble problem of orthopaedic waiting times. This is based on excellent communication and collaboration, with a clear aim of improving patient care that is evidence based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 7 publications
3
46
0
Order By: Relevance
“…Earlier studies state that communication is central and working in the same premises is the most successful way to achieve quicker and better outcomes at a lower cost. 4,5,16,19,[29][30][31][32] To our knowledge, this is the first trial that has evaluated the effects of combined manual therapy performed under own diagnostic, treatment and management responsibility, for patients with musculoskeletal disorders in outpatient orthopedic waiting lists. Further research is required to establish clinical guidelines for different musculoskeletal disorders and to investigate to which extent manual therapy may reduce orthopedic outpatient waiting lists and to perform cost analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies state that communication is central and working in the same premises is the most successful way to achieve quicker and better outcomes at a lower cost. 4,5,16,19,[29][30][31][32] To our knowledge, this is the first trial that has evaluated the effects of combined manual therapy performed under own diagnostic, treatment and management responsibility, for patients with musculoskeletal disorders in outpatient orthopedic waiting lists. Further research is required to establish clinical guidelines for different musculoskeletal disorders and to investigate to which extent manual therapy may reduce orthopedic outpatient waiting lists and to perform cost analyses.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[11][12][13] Results from studies in integrative medicine, a complement to the traditionally most common way to take care of musculoskeletal problems (with general practitioners, physiotherapists, and orthopedic surgeons), have also shown that it is possible to have better treatment effects and decreased waiting periods as well as patient satisfaction. [14][15][16][17][18][19] A British project introduced acupuncture, homeopathy, and osteopathy within a hospital and established referral indicators. Statistical differences in scores were found between a treatment and a control group on all short form (SF)-36 AQ3 scales except for physical function regarding health status favoring integrative medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] In the United Kingdom, care teams using physiotherapists with an extended scope of practice have reduced wait times, lowered direct hospital costs owing to a reduction in diagnostic tests, provided more advice and reassurance than physician counterparts, and had high levels of patient satisfaction. 19,20 At our centre, we have employed advanced-practice physiotherapists (APPs) in the arthroplasty program for 10 years and in the shoulder clinic for 5 years, with reliable triage and high levels of patient satisfaction. 18,21,22 Using physiotherapists to perform spinal triage is not a new concept.…”
mentioning
confidence: 99%
“…11,12 This means that surgeons spend a considerable amount of time providing expertise for diagnosis and management of musculoskeletal injuries, arth ritis and other conditions, 13 which could be reduced with the help of the PAs. Because the PAs understand presur gical expectations, disease processes, treatment algorithms, surgical procedures and techniques, and rehabilitative expectations and protocols, consistent communication of information from the orthopedic team is relayed to patients.…”
Section: Preoperative Clinicmentioning
confidence: 99%